2010
DOI: 10.1016/j.jpeds.2010.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Abnormalities in Adolescents with Type 1 Diabetes: A Biomarker for Vascular Sequelae?

Abstract: Objective To evaluate whether counts of circulating colony forming unit-endothelial cells (CFU-ECs), cells co-expressing CD34, CD133, and CD31 (CD34+CD133+CD31+), and CD34+CD45− cells are altered in adolescents with type 1 diabetes and if the changes in counts correlate with endothelial dysfunction. Study design Adolescents with diabetes (ages 18 to 22 years) and race- and sex-matched control subjects were studied. We assessed circulating CFU-ECs, using colony assays, and CD34+CD133+CD31+ and CD34+CD45− cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
4
19
2
Order By: Relevance
“…In addition, fewer pro-angiogenic circulating progenitor cells in cord blood of infants born very premature is associated with an increased risk of developing BPD, which is characterised by impaired alveolar development and decreased DLCO [17][18][19]. This finding of a relationship between circulating progenitor cells and vascular function in infants would be consistent with our previous report that having fewer CHSPCs was associated with decreased vascular function in adolescents with diabetes [9]. Mobilisation of circulating pro-angiogenic cells may be an effective strategy to induce lung growth, particularly in infants with impaired alveolar development; however, more mechanistic studies are required [4].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, fewer pro-angiogenic circulating progenitor cells in cord blood of infants born very premature is associated with an increased risk of developing BPD, which is characterised by impaired alveolar development and decreased DLCO [17][18][19]. This finding of a relationship between circulating progenitor cells and vascular function in infants would be consistent with our previous report that having fewer CHSPCs was associated with decreased vascular function in adolescents with diabetes [9]. Mobilisation of circulating pro-angiogenic cells may be an effective strategy to induce lung growth, particularly in infants with impaired alveolar development; however, more mechanistic studies are required [4].…”
Section: Discussionsupporting
confidence: 88%
“…We have previously demonstrated that the normal physiological increase in pro-angiogenic (p) CHSPCs during pregnancy is impaired in females with gestational diabetes mellitus and pCHSPCs were lower in cord blood of mothers with gestational diabetes mellitus [8]. In addition, we have demonstrated that adolescents with diabetes mellitus have impaired endothelium-dependent vasodilation, which correlates with reductions in the ratio of pro-angiogenic to non-angiogenic circulating progenitor cells [9]. Evaluating angiogenic cells in infants has been limited by the previous need for large volumes of blood to identify angiogenic circulating progenitor cells; however, we have previously described a multiparameter flow cytometry technique to identify pCHSPCs in 1-mL blood samples [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…That observation seems sobering because these measures are currently widely used in the clinic for assessment of risk of future microvascular and macrovascular diseases. However, other studies on young T1DM patients also failed to demonstrate these types of relations (23,34). Altogether, these observations suggest that other factors besides 'average' of glycaemic values (such as glucose variability) may affect circulating progenitor cell numbers and vascular reactivity at a given moment in time.…”
Section: Discussionmentioning
confidence: 89%
“…116 Endothelial dysfunction has been demonstrated in numerous studies in adolescents with T1DM. 96,117 Nonultrasound methods for assessing endothelial function, including peripheral arterial tonometry, 118,119 and laser flow Doppler studies 120 have demonstrated similar case-control differences. Poor endothelial function was associated with higher HbA 1c 121 and poor fitness level 122 but was not related to inflammation.…”
mentioning
confidence: 96%